Analyzing the determinants of operational efficiency in VN30 companies on the Vietnamese stock exchange - Nguyen, Kim Thi Chung; Nguyen, Thi Thuy Huong; Dao, Thi Ho Huong; Truong, Quoc Cuong; Nguyen, Dieu Linh (Edelweiss Applied Science and Technology, 2025)
This study analyzes the factors that influence the business performance of VN30 companies listed on the Vietnamese stock market between 2010 and 2020. The primary objective is to evaluate how macroeconomic factors, such as GDP, inflation, interest rates, and exchange rates, along with corporate governance factors like credit risk, operational risk, and liquidity risk, affect business performance, measured by return on assets (ROA). To assess these effects, the study uses the FMOLS regression model for long-term impacts and the ECM model for short-term effects. The results suggest that in the long run, GDP has a slight positive impact, though not statistically significant, while inflation and credit risk have a significantly negative effect on performance. Exchange rates and interest rates, on the other hand, do not exhibit clear statistical significance. Based on these findings, the study offers several policy recommendations aimed at improving the performance of companies, particularly in managing inflation and credit risk, to strengthen their business outcomes in the context of Vietnam’s evolving economic environment.